Atomically precise graphene nanoribbon heterojunctions from a single molecular precursor - Nguyen, Giang D.; Tsai, Hsin-Zon; Omrani, Arash A.; Marangoni, Tomas; Wu, Meng; Rizzo, Daniel J.; Rodgers, Griffin F.; Cloke, Ryan R.; Durr, Rebecca A.; Sakai, Yuki; Liou, Franklin; Aikawa, Andrew S.; et al. (Nature nanotechnology, 2017)
The rational bottom-up synthesis of atomically defined graphene nanoribbon (GNR) heterojunctions represents an enabling technology for the design of nanoscale electronic devices. Synthetic strategies used thus far have relied on the random copolymerization of two electronically distinct molecular precursors to yield GNR heterojunctions. Here we report the fabrication and electronic characterization of atomically precise GNR heterojunctions prepared through late-stage functionalization of chevron GNRs obtained from a single precursor. Post-growth excitation of fully cyclized GNRs induces cleavage of sacrificial carbonyl groups, resulting in atomically well-defined heterojunctions within a single GNR. The GNR heterojunction structure was characterized using bond-resolved scanning tunnelling microscopy, which enables chemical bond imaging at T = 4.5 K. Scanning tunnelling spectroscopy reveals that band alignment across the heterojunction interface yields a type II heterojunction, in agreement with first-principles calculations. GNR heterojunction band realignment proceeds over a distance less than 1 nm, leading to extremely large effective fields. Bottom-up fabrication of GNR heterojunctions exhibiting atomically perfect heterojunction interfaces can be obtained from a single molecular precursor via post-growth modification